IJCM_368A: Knowledge, attitude and practice on organ donation among college students in madurai district, Tamil Nadu - a cross-sectional study - Prabhakaran S; Priya SD; Muthuraman Kannan A (Wolters Kluwer Medknow Publications, 2024)
Background: The mainstay treatment for end-stage organ disease is transplantation as it improves the quality of life for organ recipients1. Though National Organ Transplant Programme is functioning well, the number of end stage organ deaths stands at 500000/year. Hence the need of present study conducted among students as they serve as health messengers for any Public Health Programme to succeed. Objective: 1. To assess Knowledge, Attitude and Practice [KAP] on Organ Donation among College students, Madurai district. 2. To determine association between Socio-Demographic characters like Gender, Age, Religion with Knowledge and Attitude on Organ Donation among the study population. Methodology: This Cross-sectional study on organ donation was conducted among 550 Arts College students in Madurai District from September to October 2023 using Multi stage Sampling and Sample size was estimated by using Kinge A et al3. After obtaining informed consent, study population was interviewed using Semi Structured Questionnaire containing 4 sections including KAP and Socio Demographic Profile. For positive questions, each Correct answer was given 1 mark and incorrect answer as 0. Reverse Scoring was assigned to Negative Questions. Data entered in Excel and analysed using SPSS version 21.0. Results: The mean age of participants was 19.57± 2.9 with males 44.54% and Females 55.45%. Hindus were 85.27%, Muslims 6% and Christians 8.72%. Out of 550 Participants, 40.36%(n=222) had adequate Knowledge with mean score of 5.08 Â± 0.53, 90.81% (n=505) had Positive attitude, 5 %(n=28) had taken pledge. Chi-square showed statistically significance between Knowledge and Age, gender Conclusion: Regular IEC activities and inclusion of Organ donation as a part of education curriculum are needed to further improve awareness.